THE ANALYSIS OF ADDED VALUE OF MILLED HYBRID CORN PROCESSING BISI 2 (ZEA MAYS L.) AT FARMER HOUSEHOLDS INDUSTRY IN THE VILLAGE WOWOLI TOARI DISTRICT OF KOLAKA - Yuli Purbaningsih (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
Analysis of the Value Added of Milled Hybrid Corn Processing (Zea mays L.) Bisi2 on Household Industrial Farming in the village Wowoli Toari District of Kolaka. This study aims to determine the value-added of milled Hybrids corn processing (Zea mays L.) Industry Bisi2 on farm households in the village Wowoli Toari District of Kolaka. This study used a descriptive method of analysis is a research method that focuses on solving the problems that exist in the present. the data initially collected in the analysis, collated and then described so as to provide answers about the phenomena - phenomena that occur. Further explaining is about the relationship, testing hypotheses and draw conclusions from the analysis that was obtained. Based on the research that has been done on an industrial farm household processing of corn flour in the village Wowoli District of Toari Kolaka of two industry can be concluded that industry farm household processing of corn flour gives the profit earned per 3 times the production process for one month is Rp 3.198 million. Employers’ added value-processing industry of farm households grits Rp 1,100 / kg of raw material used. This added value is the profit earned by the farm household Industrial processing of corn flour in 1 kilogram of raw materials usage. Farm household industrial processing corn into grits in the village Wowoli provides a distinct advantage for corn farmers, where farmers can sell corn to corn processing industry with a short distance to the industry processing industry of farm households grits with higher prices.